Age and cause‐of‐death contributions to area socioeconomic, sex and remoteness differences in life expectancy in New South Wales, 2010–2012. (31st January 2018) - Stephens, Alexandre S.; Blyth, Fiona; Gupta, Leena; Broome, Richard A.
Abstract: Objectives: To determine age group‐ and cause‐of‐death‐specific contributions to area socioeconomic status (SES), sex and remoteness life expectancy inequalities. Methods: Mortality and estimated residential population data from New South Wales, Australia, over 2010–2012 was used to calculate life expectancy. Inequalities by sociodemographic groups were partitioned into age group‐ and cause‐of‐death‐specific contributions. Results: The largest contributions to SES differentials in life expectancy were observed at 60–84 years of age; for cancer, cardiovascular, endocrine and respiratory causes of death; and additionally external causes of death for males. Sex inequalities ranged from 3.6 to 5.2 years, with common causes of death such as cardiovascular disease and cancer in late adulthood (60+ years) accounting for the bulk of the differences. Smaller differences in life expectancy were observed by remoteness, with the largest contributions observed in ages 85 years and above, and for cardiovascular, mental, cancer and external causes of death. Conclusions: Common causes of death in late adulthood accounted for the bulk of life expectancy inequalities. Implications for public health: Development of policy and interventions aimed at addressing social determinants, such as proposed by the WHO's Global Plan of Action, are needed to help reduce sociodemographic inequalities in lifespan.